Clinical Characteristics of Colorectal Polyp in Thai Children: A Retrospective Study - Waitayakul S. (2014)
Background: It was believed that more than 90 per cent of children with colorectal polyp had a single lesion, located in the rectosigmoid colon, therefore, sigmoidoscopy with polypectomy was the treatment of choice. After a wide use of pediatric colonoscopy, this concept has been changed. Material and Method: This study was aimed to describe clinical characteristics of colorectal polyp in Thai children. Medical records of children with colorectal polyp were retrospectively reviewed. Comparison between polyposis coli and children with less than 5 polyps were also analyzed. Results: There were 93 patients, 43 females and 50 males. The average age was 5.1 years. Lower GI bleeding and prolapse of rectal polyp comprised the two most common presentations, 93.5 and 39.8 per cent, respectively. The mean duration of symptoms was 5.6 months. Only 50.6 per cent had rectal polyp noted by digital examination. Investigations included sigmoidoscopy (n = 77), colonoscopy (n = 16), and barium enema (n = 16). Eight per cent of the cases had more than 5 polyps. Location of the polyps was noted in the rectosigmoid colon (88.2%), descending colon (4.3%), right-sided colon (4.3%), and pancolonic (3.2%). Of all the patients, 11.8 per cent had the polyp above the rectosigmoid region, whereas 50 per cent of those who underwent colonoscopy (n = 16) had the polyps noted proximal to this region. Older age, lower hematocrit, and more frequent right-sided polyps were significantly associated with polyposis coli (p < 0.05). Only 2 patients with polyposis coli were treated by colectomy. Histopathology included juvenile polyp (95%), inflammatory pseudopolyp (2.5%), and hyperplastic polyp (2.5%). Conclusion: Most of the children with colorectal polyp had juvenile polyp that is commonly found in the rectosigmoid colon. However, a significant number of patients had carrying polyps proximal to the rectosigmoid region, which would be easily missed by sigmoidoscopy. With the concern of malignancy change particularly in children with polyposis coli, routine colonoscopy should be considered as an initial investigation in children with colorectal polyp.